La edición perdida de Wieland en España (ca. 1818) - José Manuel Correoso Rodenas (Cuadernos de Ilustración y Romanticismo)
The main objective of this article is to recover an early 19th century Spanish edition of one of the first important novels of the literature produced in the United States: Wieland, by Charles Brockden Brown. One of the reasons why Vieland has been obviated by most of the critics for two centuries is because it was translated from a previous French version. Finally, the publication of this novel in a cultural panorama still influenced by the Spanish Inquisition makes the relevance and importance of this article even higher.